Jino Batik Wayang Kayu Home Industry in Jarum, Bayat, Klaten - Salsabila, Intan; Zuhdi, B Muria (Universitas Negeri Yogyakarta, 2024)
This research describes the production process and characteristics of batik wayang kayu (batik wooden puppet) in terms of canting strokes, filler patterns, and color schemes. A qualitative descriptive method was employed, with data collection techniques including observation, interviews, and documentation. Data validity was ensured through persistent observation and triangulation. The findings reveal that the production process of batik wayang kayu is broadly similar to that of traditional batik, with differences mainly in the pelorodan (wax removal) and finishing stages. The canting strokes in batik wayang kayu at Jino Batik Home Industry are dominated by curved and wavy lines, with variations in thick and thin strokes creating a fluid and graceful impression. The filler patterns used are highly diverse and tailored to specific sections of the wooden puppet batik. The color schemes in batik wayang Kayu are divided into three categories: primary colors for the puppet's body, supporting colors for the puppet's attributes, and accent colors used in the isen-isen (decorative elements), often applied through canting strokes. This study highlights the unique artistic qualities of batik wayang kayu and cultural significance, offering insights into its intricate craftsmanship and aesthetic appeal.